PRODUCTION AND SECURITY OF FOOD IN GLOBAL CIRCLE - ILO MOSES I. OLATUNDE (International Studies Journal)
Food is indispensable to the growth and development of the people across the world. It remains first in the affairs of man regardless of one's background. A nation without food will experience poverty, hunger and malnutrition which are inimical to overall growth and development. Food production is the cultivation of plants and rearing of animal as well as preparing them for human consumption. The Food and Agricultural Organization has been preaching the need for the people around the world to be food secured. Consequently, the developed countries have been on the vanguard of food security by putting strong policies in place to achieve it to her citizen. Conversely, in developing countries especially in Africa, food production has been given less attention by the government owing to bad governance that led to the alarming increase in the prices of staple food stuffs which resulted into global food crises starting from 1970s. This paper focuses on Nigeria which her food production is contrary to the global best practices leading to food insecurity in the country and the developed countries have been using food as a global politics against the country that is food in-secured. The paper employed primary and secondary historical research to explore the gargantuan challenges of food production in Nigeria despite her abundance resources to achieve food production for her citizens and for export. The work argues that Nigeria should break away from her dependency syndrome and embark on modern food production for her citizens regardless of interdependency of nations and Ecological Armageddon that threatening the environment. The work concludes that Nigeria needs good leaders that are more proactive to food production rather than politicizing it. The paper recommends that government should synchronize both internal and external remedies of large scale food production to promote food sufficiency that can enhance peace and development in the comity of nations.